Pharmacological Effects and Chemical Constituents of Bupleurum - Sun, Peng; Li, Yijie; Wei, Sheng; Zhao, Tingting; Wang, Yang; Song, Chunhong; Xue, Ling; Wang, Fushun; Xiao, Lingyun; Wu, Jibiao; Qiao, Mingqi (Mini Reviews in Medicinal Chemistry, 2019)
Radix Bupleuri has been used in traditional Chinese medicine for thousands of years, with confirmed curative effects. This plant is also used in healthy food and cosmetics. A recent increase in studies of Radix Bupleuri's chemical constituents (mainly comprising flavonoids, lignins, phenyl propanol derivatives, triterpenoid saponins, and volatile oils) and pharmacological effects motivates the aim of the present study: to review the chemical components and pharmacological effects of Radix Bupleuri. Our review found that Radix Bupleuri exhibits diverse pharmacological effects. More than 281 components have been isolated from Radix Bupleuri, including 15 flavonoids, 430 lignins, 12 phenyl propanol derivatives, 66 triterpenoid saponins, and 158 volatile oils.
Keywords: phenyl propanol derivatives